Implementation of Practical Training for Hajj Rituals in Singgahan District, Tuban Regency, from the Perspective of Fiqh of Worship - Alfithra Madya Fasa; Abdul Rozaq (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This research is motivated by the importance of understanding the Islamic jurisprudence of worship in the implementation of Hajj rituals, considering that Indonesia is the country with the largest number of Hajj pilgrims in the world. Singgahan District, Tuban Regency, was designated as the center for inter-district provision, presenting a new dynamic that is interesting to study from the perspective of Islamic jurisprudence of worship, particularly the consistency of the application of the Shafi'i school of thought. This study aims to evaluate how the implementation of the provision of Hajj ritual practices is carried out systematically and whether pilgrims truly understand the Islamic jurisprudence aspects of their Hajj rituals. The method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the provision is carried out with a structured management pattern, the Islamic jurisprudence material is delivered according to the Shafi'i school of thought, and the guides strive to avoid the practice of talfiq so that the pilgrims' worship is valid according to sharia. The policy of combining provision between sub-districts has proven effective in improving the quality of guidance and resource efficiency, although it still faces challenges such as differences in the educational background of pilgrims and geographical accessibility. Education on rukhshah is also provided in emergency situations while maintaining the boundaries of the madhhab (Islamic school of thought). The results of this study are important as a reference for developing a national Hajj training strategy that is based on Islamic jurisprudence, effective, and contextualized to local conditions.